Penggunaan TikTok dan YouTube sebagai Media Edukasi Pangan Kelompok Usia Remaja dan Dewasa - Meiliana; Rika Pratiwi; Mellia Harumi (Servirisma, 2021)
Using social media to obtain information or learn something has become a trend in various circles of society. Educational activities using social media Tiktok and YouTube can be carried out as an activity to transfer knowledge from academics to the wider community. Knowledge about Indonesian staple food (rice) and Semarang specialties (Lumpia Semarang) needs to be conveyed to the younger generation, starting from history, culture, nutrient content, and processing methods. The purpose of this community service activity through social media is to increase the knowledge of the adolescent and adult age groups regarding the function of food, processing methods, and how to consume good and healthy food through TikTok and YouTube educational videos; create a media to socialize traditional Indonesian food as healthy food; and make learning media about food science and technology for the wider community. The results of this activity are 2 YouTube videos uploaded on the FoodTech Unika YouTube channel and 4 TikTok videos uploaded to the TikTok account @foodtechunika.